2003
DOI: 10.1038/sj.bjc.6601159
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and understanding of disease status among cancer patients of different ethnic origin

Abstract: Patients managed in European or North American cancer centres have a variety of ethnic backgrounds and primary languages. To gain insight into the impact of ethnic origin, we have investigated understanding of disease status and quality of life (QoL) for 202 patients. Patients completed questionnaires in their first language (52 English, 50 Chinese, 50 Italian, 50 Spanish or Portuguese), including the Functional Assessment of Cancer Therapy -General (FACT-G) QoL instrument, questions about disease status, expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…In other studies, stoma and nonstoma patients were compared, but a great proportion of these patients had undergone high anterior resection, which is associated with better function and quality of life than low anterior resection. 1,2,4,19 Second, to avoid cultural differences, 12 only patients living on the French territory were eligible for our study. Finally, instead of relying only on the global impact of the surgery or stoma status on QoL variables, we also considered individual patient characteristics by conducting differential statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, stoma and nonstoma patients were compared, but a great proportion of these patients had undergone high anterior resection, which is associated with better function and quality of life than low anterior resection. 1,2,4,19 Second, to avoid cultural differences, 12 only patients living on the French territory were eligible for our study. Finally, instead of relying only on the global impact of the surgery or stoma status on QoL variables, we also considered individual patient characteristics by conducting differential statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…QoL results are not easy to generalize, because the impact of a diagnosis or treatment can differ solely because of cultural difference. 3,4,7,12 Third, the impact of rectal surgery on QoL may also depend on patient-related factors, such as age, gender, education, or marital status. 13 Previous studies performed on patients sustaining various malignancies have shown associations between QoL scores and age, 14,15 education level, 13 marital status, 13,16 and social support.…”
mentioning
confidence: 99%
“…The researchers, Fayers et al, proposed several checks to apply to the observed data before using the simple mean imputation [1] Despite a widely recognised need to assess perception of HRQoL in relation to cultural, ethnic and religious characteristics, not much is known about this in non-Caucasian populations [9,10]. A few studies investigated HRQoL and patterns of responses to HRQoL questions in African-American and Hispanic patients [2,8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Patients in many cancer centers in North America and Europe have a variety of ethnic and language backgrounds [2]. Quantitative confirmation of equivalence between different language versions of the same instrument is an important issue in the development and application of health-related quality-of-life (HRQoL) measures, both for use within multiethnic societies and for multi-country studies and cross-cultural comparison [3].…”
Section: Introductionmentioning
confidence: 99%